Bilingual model of future specialists’ training by means of artistic design (Educational Dimension, 2020)
The article presents the authors’ bilingual model of future specialists’ training by means of artistic design. It outlines the content, forms, methods, criteria, and indicators of future specialists’ training in the conditions of bilingual educational process. The authors demonstrate that the development of the bilingual model contributed to the variety of students’ artistic and creative activities forms (team, group, individual) and to a wide range of methods used. The formation of the analyzed skills manifests itself in the level scale (primary, sufficient, high). The primary level of creative skills formation is realized on the basis of the developed criteria (motivation-oriented, content-procedural, evaluative-reflexive). The experimental study was carried out in several stages using theoretical, empirical methods of research. The authors also used the Pearson’s consistency criterion x2 to analyze statistical hypotheses based on observational data. The research outlines the levels of future specialists’ abilities development (association, visual (figurative) creativity, transformations, variability of thinking). The authors used the N. Vyshniakova and R. Tkach’s "Creativity" test, the S. Zievert’s "Freedom of associations" modified test.
Keywords: model; bilingual model of training of future specialists; audio-lingual method; communicative method; professional diagram of preschool and primary education specialists; artistic design